Analyzing Evaluation Process in Secondary School Geography of India - Alam, Sarfaraz; Sukhvinder (National Geographical Journal of India, 2022)
The process of evaluation of students is closely linked to their teaching-learning process in schools. However, the nature of evaluation techniques in a subject depends to an extent on grades at which it is taught as well as its philosophical and methodological orientation. In lower grades, for example, the focus is more on short and descriptive questions compared to higher grades where long and explanatory questions become important. The nature of school geography is different from other subjects for it focuses mainly on the spatial dimension of reality. For learning the spatial dimension of reality of the earth, maps and globes are the key teaching tools. While most techniques of evaluation in school geography are similar to other school subjects, it also uses certain techniques for evaluating students which are generally not popular in other subjects. This paper discusses use of various techniques of evaluation in school geography. It analyses how techniques of evaluation vary with grades. It identifies those techniques of evaluation that are unique to school geography. The study informs that mapping, map reading and fieldbased exercises are generally associated with geography